2020
DOI: 10.1007/978-981-15-4477-4_3
|View full text |Cite
|
Sign up to set email alerts
|

A Continuously Variable Transmission System Designed for Human–Robot Interfaces

Abstract: Continuously Variable Transmission (CVT) systems are being used for many applications such as automotive transmissions, robotics, aerospace. In an ideal condition, these systems have the potential to provide continuously varying power transmission within a predefined limit. This transmission is accomplished with the help of friction, belt or gear systems. CVT can find application in a human-robot interface if design criteria such as backdrivability, independent output position and impedance variation, shock ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In order to validate the working principle, an initial prototype is manufactured and proof of design experiment is conducted to observe if the same amount of torque can be transmitted in both CW and CCW directions. This initial experiment validated the performance of the new CVT design, and it was shown that bidirectional power transmission and independent transmission ratio and position variation was accomplished (Mobedi and Dede, 2018). (Mobedi and Dede, 2018) In this initial prototype, the spheres are housed inside a carriage system.…”
Section: Working Principle Of the Novel Cvtmentioning
confidence: 76%
See 4 more Smart Citations
“…In order to validate the working principle, an initial prototype is manufactured and proof of design experiment is conducted to observe if the same amount of torque can be transmitted in both CW and CCW directions. This initial experiment validated the performance of the new CVT design, and it was shown that bidirectional power transmission and independent transmission ratio and position variation was accomplished (Mobedi and Dede, 2018). (Mobedi and Dede, 2018) In this initial prototype, the spheres are housed inside a carriage system.…”
Section: Working Principle Of the Novel Cvtmentioning
confidence: 76%
“…This initial experiment validated the performance of the new CVT design, and it was shown that bidirectional power transmission and independent transmission ratio and position variation was accomplished (Mobedi and Dede, 2018). (Mobedi and Dede, 2018) In this initial prototype, the spheres are housed inside a carriage system. This carriage system is moved along a linear path to change the transmission ratio.…”
Section: Working Principle Of the Novel Cvtmentioning
confidence: 76%
See 3 more Smart Citations